Evolution of the modern baboon (Papio hamadryas): A reassessment of the African Plio-Pleistocene record. Issue 122 (September 2018) - Gilbert, Christopher C.; Frost, Stephen R.; Pugh, Kelsey D.; Anderson, Monya; Delson, Eric
Abstract: Baboons ( Papio hamadryas) are among the most successful extant primates, with a minimum of six distinctive forms throughout Sub-Saharan Africa. However, their presence in the fossil record is unclear. Three early fossil taxa are generally recognized, all from South Africa: Papio izodi, Papio robinsoni and Papio angusticeps. Because of their derived appearance, P. angusticeps and P. robinsoni have sometimes been considered subspecies of P. hamadryas and have been used as biochronological markers for the Plio-Pleistocene hominin sites where they are found. We reexamined fossil Papio forms from across Africa with an emphasis on their distinguishing features and distribution. We find that P. robinsoni and P. angusticeps are distinct from each other in several cranial features, but overlap extensively in dental size. Contrary to previous assessments, no diagnostic cranio-mandibular material suggests these two forms co-occur, and dental variation at each site is comparable to that within P. h. ursinus, suggesting that only one form is present in each case. P izodi, however, may co-occur with P. robinsoni, or another Papio form, at Sterkfontein Member 4. P izodi appears more primitive than P. robinsoni and P. angusticeps . P. robinsoni is slightly distinct from P. hamadryas subspecies in its combination of features while P. angusticeps might be included within one of the modern P. hamadryas varieties (i.e., P. h. angusticeps ). No definitive Papio fossils are currently documented in eastern Africa until the Middle Pleistocene, pointing to southern Africa as the geographic place of origin for the genus. These results have implications for Plio-Pleistocene biochronology and baboon evolution.